Transient Diabetes Insipidus in a Preterm Neonate: An Uncommon Cause of Neonatal Shock - Gouda Ankula Prasad Kartikeswar; Dhyey J Pandya; Ashwini T Mehetre; Sandeep Kadam (Wolters Kluwer Medknow Publications, 2022)
Background: Diabetes insipidus (DI) is a disorder of water homeostasis due to insufficient production or inappropriate action of vasopressin. Central DI (CDI) develops due to intracranial causes such as hypoxic-ischemic encephalopathy, meningitis, and intraventricular hemorrhage. Manifestations such as polyuria, polydipsia, and irritability may not be obvious in preterm infants, resulting in delayed recognition and difficulty in establishing diagnosis. Clinical Description: A 1.4 kg preterm girl delivered by cesarean section for a significant nonstress test (but normal Apgar scores) was admitted for very low birth weight and preterm care. Initial clinical examination was normal, and the baby remained euglycemic. The neonate developed shock and fever on the 3rd day of life without any apparent cause. Management: DI was suspected on identification of hypernatremia (150 mEq/L) and polyuria (9 mL/kg/h). The urine osmolality was low (62.54 mOsmol/kg), despite high serum osmolality (312 mOsmol/kg) confirming the diagnosis. An increase in urine osmolality by >50% following oral desmopressin (5 μg/kg/day) suggested CDI. This was continued until the baby became asymptomatic and urine/serum osmolality normalized. A trial of discontinuation of desmopressin did not lead to recurrence of symptoms. Magnetic resonance imaging brain showed features of subacute hypoxic insult and absent posterior pituitary bright spot. After 7 months of follow-up, she is asymptomatic without any treatment, and her growth and development are age appropriate. Conclusion: A high index of suspicion of CDI should be kept in neonates presenting with unexplained shock, fever, hypernatremia, and polyuria.